Socioeconomic status in life course is associated with dental appearance dissatisfaction - Luiz Alexandre CHISINI; Fabiana VARGAS-FERREIRA; Giulia Tarquinio DEMARCO; Karen Glazer PERES; Marco Aurélio PERES; Bernardo Lessa HORTA; Flávio Fernando DEMARCO (Sociedade Brasileira de Pesquisa Odontológica, 2024)
Abstract The present study aimed to investigate the prevalence of dissatisfaction with dental appearance among 24-year-old Brazilian adults and the associated factors in life course. A subsample (n = 720) of the 1982 Pelotas Birth Cohort in southern Brazil was investigated at the ages of 15 and 24 years using clinical (caries and periodontal) examinations and interviews. The outcome was dissatisfaction with dental appearance at the age of 24 years. Covariate variables included socioeconomic factors, oral health, and dissatisfaction with general appearance collected during different periods of life. Poisson regression models with robust variance were applied. The prevalence of dissatisfaction with dental appearance was 43.5% (95%CI: 39.8-47.1). Individuals with downward income mobility (PR = 1.22, 95%CI: 1.07-1.79) and those always poor (PR = 1.21, 95%CI: 1.00-1.57) presented a higher prevalence of dissatisfaction with their dental appearance even after oral health variables and dissatisfaction with general appearance were controlled for. Moderate/severe malocclusion at 15 years (PR = 1.34, 95%CI: 1.13-1.59), highest experience of untreated dental caries at 24 years (PR = 1.82, 95%CI: 1.46-2.27), and dental pain experience at 24 years (PR = 1.29, 95%CI: 1.22-1.75) were associated with the outcome. Also, the prevalence of dissatisfaction with dental appearance was 20% higher (PR = 1.20, 95%CI: 1.01-1.43) among those dissatisfied with their general appearance. Our findings demonstrated a high prevalence of dissatisfaction with dental appearance among young adults. Lifetime economic disadvantage and dental problems (malocclusion at 15 years, untreated dental caries at 24 years, and dental pain at 24 years) were associated with dissatisfaction with dental appearance among young adults.